Structure–activity relationship studies of citalopram derivatives: examining substituents conferring selectivity for the allosteric site in the 5‐HT transporter. (8th February 2016) - Larsen, M Andreas B; Plenge, Per; Andersen, Jacob; Eildal, Jonas NN; Kristensen, Anders S; Bøgesø, Klaus P; Gether, Ulrik; Strømgaard, Kristian; Bang‐Andersen, Benny; Loland, Claus J
Abstract : Background and Purpose: The 5‐HT transporter (SERT) is a target for antidepressant drugs. SERT possesses two binding sites: the orthosteric (S1) binding site, which is the presumed target for current SERT inhibitors, and an allosteric (S2) site for which potential therapeutic effects are unknown. The antidepressant drug citalopram displays high‐affinity S1 binding and low‐affinity S2 binding. To elucidate a possible therapeutic role of allosteric inhibition of SERT, a drug that specifically targets the allosteric site is required. The purpose of this study was to find a compound having higher selectivity towards the S2 site. Experimental Approach: We performed a systematic structure–activity relationship study based on the scaffold of citalopram and the structurally closely related congener, talopram, which shows low‐affinity S1 binding in SERT. The role of the four chemical substituents, which distinguish citalopram from talopram in conferring selectivity towards the S1 and S2 site, respectively, was assessed by determining the binding of 14 citalopram/talopram analogous to the S1 and S2 binding sites in SERT using membranes of COS7 cells transiently expressing SERT. Key Results: The structure–activity relationship study revealed that dimethyl citalopram possesses the highest affinity for the allosteric site relative to the S1 site in SERT and has approximately twofold selectivity for the allosteric site relative to the S1 site in SERT. Conclusions and Implications: The compound could be a useful lead for future synthesis of drugs with high affinity and high selectivity towards the allosteric binding site.